(untitled) (Journal of humanities and social sciences exploratio, 2026)
The protection of the legitimate rights and interests of minors is an important part of the construction of a law - based society and the modernization of social governance. As a key carrier for integrating multiple resources and bridging the "last mile" of the protection of minors’ rights and interests, the construction quality of the new - type legal aid platform directly determines the actual implementation effect of the judicial protection of minors. By defining the core connotation of the new - type legal aid platform for minors, sorting out the theoretical foundations such as the maximization of children’s interests and collaborative governance, and combining the current situation of legal aid practice for minors in China, this paper analyzes the practical dilemmas faced by the platform construction from four dimensions: legislation, mechanism, service, and technology, and proposes targeted and operable optimization paths. The research confirms that for the construction of the new - type legal aid platform for minors, it is necessary to take the improvement of legislation as the guarantee, the reconstruction of the mechanism as the core, the upgrading of services as the key, and the empowerment of technology as the support, so as to help the platform transform from "passive response" to "active service" and from "single legal aid" to "diversified comprehensive protection", and build a solid legal barrier for the healthy growth of minors.